Application of Simulation Program to Increase Efficiency Production Line Core - Na Badalung, Chirawat; Thongsang, Supakit; Meesil, Ladapan; Wasaram, Charinya; Samattapapong, Nara; Pontaweechai, Pornniwat; Klomjit, Prachuab (Rajamangala University of Technology Tawan-ok Research Journal, 2025)
This article presents the development of a simulation model for the core production process to analyze system performance and improve production efficiency. The existing system suffers from bottlenecks, process imbalance and excessive waiting time, while lacking a systematic approach to quantitatively evaluate multiple improvement alternatives prior to actual investment decisions. The study designed a better system than the current one, which was then applied in the form of a simulation model, creating a simulation model using the Flexsim simulation program to help develop and improve the design of new work processes. The find the most appropriate way of working that can increase daily production efficiency. This research studied the production of traditional patties after finding that the production of patties was not according to the production plan and forming the pieces took 2 longer times the machine press makes employees wait. When using the results from the simulation with the Flexsim program Comparing with the current production, it is found that adding 1 Separator and 2 Combiners is the most appropriate choice. This results in increasing production efficiency by 54.8% or being able to produce 1,228 pieces per day and also reducing the number of pieces waiting before entering the next process.